A case of massive hematoma: reflections on hypermobile Ehlers-Danlos syndrome - QingHua Liu; Ganhua Zeng; Yu Xiong; Chenyang Xu (Frontiers in Medicine)
Ehlers-Danlos Syndrome (EDS) refers to a group of connective tissue disorders characterized by significant clinical and genetic variability, affecting multiple systems in the body. Classified as a rare disease, EDS includes 14 subtypes, all marked by joint hypermobility, skin extensibility, and tissue fragility. These subtypes present with a wide range of clinical manifestations and severities, including frequent joint dislocations, scoliosis, arterial dissections, and organ ruptures. Hypermobile EDS (hEDS) is the most common subtype, with newly established clinical diagnostic guidelines. In this case, a patient presented with minor hemoptysis over 8 h, and a chest CT scan revealed a massive hematoma in the left lower lung. Due to the complexity and varied presentations of EDS, misdiagnosis is common. This report shares our experience with diagnosis and treatment in this case, highlighting the importance of increasing awareness for improved survival outcomes.